2017
DOI: 10.1016/j.clim.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of HCV-specific antibody responses in HIV/HCV patients on long-term antiretroviral therapy

Abstract: Antibody responses have not been fully characterised in chronically HIV/HCV patients receiving antiretroviral therapy (ART). Seventeen HIV/HCV patients receiving ART were followed for a median (range) interval of 597 (186-766) weeks. Prior to ART, HIV/HCV patients had lower levels of antibodies reactive with HCV core and JFH-1, and lower genotype cross-reactive neutralising antibodies (nAb) titres, than HCV patients. Levels of JFH-1 reactive antibody increased on ART, irrespective of CD4 T-cell counts or chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Additionally, Lee et al . found that HCV-nAbs against JFH-1 correlated positively with baseline CD4+ T-cell counts and increased after cART in HIV/HCV-coinfected patients, regardless of the baseline CD4+ T-cell counts 46 . In addition to the T-cell, HIV infection induces dysregulation of B cells and damage of lymphoid organs, which endangers the humoral immune response 4750 .…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, Lee et al . found that HCV-nAbs against JFH-1 correlated positively with baseline CD4+ T-cell counts and increased after cART in HIV/HCV-coinfected patients, regardless of the baseline CD4+ T-cell counts 46 . In addition to the T-cell, HIV infection induces dysregulation of B cells and damage of lymphoid organs, which endangers the humoral immune response 4750 .…”
Section: Discussionmentioning
confidence: 88%